Another man in the house: Oedipal phantasies and the male observer in an infant observation. Issue 1 (2nd January 2017) - Zuppardi, Sam
Abstract : This paper considers the way in which powerful Oedipal phantasies come into play in any observation, arising from the disruption caused by the introduction of a new baby and a new observer into an intimate family environment. It argues that this disruption can take on an added complexity when the observer is a male. The paper uses excerpts from the author's own infant observation to demonstrate and expand upon these themes that show how Oedipal phantasies and anxieties were a prominent feature of the early months. It focuses on the dynamics arising between the observer and the parents of the baby and comments on the ways in which Oedipal anxieties and phantasies at times unbalance the observational stance, drawing the observer into something that could feel both unsettling and seductive. It also looks at some of the ways in which these anxieties can be gradually contained and managed by both the observer and family. The paper draws parallels between the observer's role and that of the therapist.